2017
DOI: 10.1097/j.pain.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Procedural pain and oral glucose in preterm neonates: brain development and sex-specific effects

Abstract: Our objectives were to determine whether procedural pain and glucose exposure are associated with altered structural and functional brain development differently in preterm males and females, and neurodevelopment at 18-month corrected age. Fifty-one very preterm neonates (22 males; median [interquartile range] gestational age 27.6 [2.0] weeks) underwent 3 serial scans including T1-weighted and resting-state functional magnetic resonance imaging (MRI) at median postmenstrual weeks: 29.4, 31.9, and 41.1. Thalamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 44 publications
9
71
0
Order By: Relevance
“…At 18 months, more invasive procedures in NICU were associated with slower thalamic growth and reduced total brain volume, particularly in VP females [10]. At 7 years of age, increased neonatal procedural pain exposure was associated with lower cortisol, primarily in boys born preterm (24)(25)(26)(27)(28)(29)(30)(31)(32) weeks GA) [36].…”
Section: Psychosocial Factors and Risk Of Future Painmentioning
confidence: 97%
See 1 more Smart Citation
“…At 18 months, more invasive procedures in NICU were associated with slower thalamic growth and reduced total brain volume, particularly in VP females [10]. At 7 years of age, increased neonatal procedural pain exposure was associated with lower cortisol, primarily in boys born preterm (24)(25)(26)(27)(28)(29)(30)(31)(32) weeks GA) [36].…”
Section: Psychosocial Factors and Risk Of Future Painmentioning
confidence: 97%
“…Different types and dose of analgesic and sedative drugs, such as opioids and benzodiazepines, can have positive and/or negative effect on outcome, as detailed in a recent review [9]. Glucose can modulate acute behavioural responses to procedural interventions, but increased numbers of tissue-breaking procedures and higher cumulative doses of glucose/sucrose have been associated with poorer neurodevelopmental outcome and altered brain structure and connectivity [10]. While it is now widely acknowledged that untreated pain can influence neurodevelopmental outcome, and adequate analgesia is required for significant painful procedures and surgery, there is currently wide variability in the use of sedative and analgesic drugs in neonatal units [9].…”
Section: Confounding Factorsmentioning
confidence: 99%
“…The infants' shoulders were also constricted up to 90 degrees, and the hands of the nurse were placed over the head close to the mouth or on the infant's face. In the oral dextrose intervention, infants received 0.5 ml of 50% dextrose by a syringe 2 min before the procedure [2]. The same nurses performed all the six heel sticks for each of the infants in all six measurements.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…Pain in newborns can cause severe problems in growth and development [1]. Procedural pain is one of the most frequent pains that infants may experience [2]. Recent research has shown that painful experiences can negatively impact infants' brains with implications on their neurodevelopment and pain reactivity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors in very preterm infants (ELGA & VLGA) include postnatal infection [Ranger et al, 2015;Zwicker et al, 2016], as well as exposure to numerous daily invasive procedures such as blood draws and line insertions, during weeks to months in the neonatal intensive care unit (NICU) [Roofthooft et al, 2014;Vinall and Grunau, 2014]. The disruption of normal intrauterine maturation by preterm birth, neonatal clinical factors, and painrelated stress alters ongoing brain development during critical periods involving prolific axonal growth, dendritic sprouting, and synapse formation [Mrzljak et al, 1992], that leads to abnormal brain morphology and activity Schneider et al, 2018;Smith et al, 2011]. Thus, to ensure proper extrauterine environment and adequate preterm interventions, it is of vital importance to understand how structural and functional preterm alterations are associated with cognitive and behavioral outcomes in children born very preterm.…”
Section: Introductionmentioning
confidence: 99%